2006
DOI: 10.1152/ajpregu.00478.2005
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength-dependent effects of evening light exposure on sleep architecture and sleep EEG power density in men

Abstract: Light strongly influences the circadian timing system in humans via non-image-forming photoreceptors in the retinal ganglion cells. Their spectral sensitivity is highest in the short-wavelength range of the visible light spectrum as demonstrated by melatonin suppression, circadian phase shifting, acute physiological responses, and subjective alertness. We tested the impact of short wavelength light (460 nm) on sleep EEG power spectra and sleep architecture. We hypothesized that its acute action on sleep is sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
139
3
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 166 publications
(159 citation statements)
references
References 35 publications
8
139
3
2
Order By: Relevance
“…The relationship between the wavelength of light and its alerting response seems to indicate a predominance of short-wavelength light (470 nm and lower) in comparison to other wavelengths Münch et al, 2006;Revell et al, 2006). Exposure to 460-nm (blue) monochromatic light for 6.5 h during the biological night (maximum levels of melatonin secretion) can substantially decrease both subjective sleepiness, improve cognitive performance in tasks of sustained attention (i.e., psychomotor vigilance task), and decrease waking EEG power density in the delta-theta frequency range (Fig.…”
Section: Short-wavelength Effects: Conventional Visual Photoreceptionmentioning
confidence: 98%
See 1 more Smart Citation
“…The relationship between the wavelength of light and its alerting response seems to indicate a predominance of short-wavelength light (470 nm and lower) in comparison to other wavelengths Münch et al, 2006;Revell et al, 2006). Exposure to 460-nm (blue) monochromatic light for 6.5 h during the biological night (maximum levels of melatonin secretion) can substantially decrease both subjective sleepiness, improve cognitive performance in tasks of sustained attention (i.e., psychomotor vigilance task), and decrease waking EEG power density in the delta-theta frequency range (Fig.…”
Section: Short-wavelength Effects: Conventional Visual Photoreceptionmentioning
confidence: 98%
“…Similarly, a 2-h evening exposure to monochromatic light of two different wavelengths (460 and 550 nm) at very low intensities resulted in more alertness during exposure at 460 nm, which further suggests a blue-shift response to light (Revell et al, 2006). However, these responses do not confine only to effects on wakefulness, but have been observed on a wide array of physiological variables, such as melatonin suppression (Lewy et al, 1980;Zeitzer et al, 2000), circadian phase shifting (Cajochen et al, 1992), nocturnal decline in EEG SWA (Münch et al, 2006;Fig. 4), and circadian gene expression (PER2) in oral mucosa (Cajochen et al, 2006).…”
Section: Short-wavelength Effects: Conventional Visual Photoreceptionmentioning
confidence: 99%
“…In a subsequent study, exposure to two 45-min pulses of bright light in the early subjective evening entrained the circadian system to a non-24-h day, indicating that intermittent pulses are highly efficient at resetting human circa dian rhythms (Gronfier et al, 2007), and can significantly contribute to efficient wakefulness. The relationship between the wavelength of light and its alerting response yielded clear superiority of short wavelength light (470 nm and lower) in comparison to other wavelengths (Cajochen et al, 2005;Mü nch et al, 2006;Revell et al, 2006a). For instance, exposure to 460-nm monochromatic light for 6.5 h during the biological night attenuated subjective sleepiness (Fig.…”
Section: Dose-and Wavelength Response Relationship Of Light Exposumentioning
confidence: 99%
“…Indeed, in humans, alertness increases with presleep blue light exposure and effects can persist for long into sleep (15)(16)(17). According to this scenario, the baseline spike rate of retinal ganglion cells would remain highest after blue light, medium after green light, and lowest after orange light, and so would the excitatory output to the downstream areas that it encodes.…”
Section: A Bold Effectmentioning
confidence: 99%
“…A few studies suggest that this may indeed happen under certain conditions. For example, alertnessreducing effects of amber light can persist for long into sleep (15)(16)(17). Another observation is that a red filter can strongly alleviate migraine pain (17), which involves the majority of the brain areas that Chellappa et al (2) found to be sensitive to prior color exposure, including the prefrontal cortex, pulvinar, and amygdala (18).…”
Section: A Bold Hypothesismentioning
confidence: 99%